BaLiZn3B3O9: a Mixed‐Cation KBe2BO3F2‐Type Zinc‐Borate with a (LiZn3B3O9)∞ Network. Issue 32 (20th August 2018) - Duan, Meihong; Xia, Mingjun; Li, Rukang
Abstract : The mixed‐cation KBe2 BO3 F2 ‐type polyborate, BaLiZn3 B3 O9, has been obtained. It was constituted by a three‐dimensional (LiZn3 B3 O9 )∞ network with perpendicularly connected (LiZn3 B3 O16 )∞ layers. Within each single layer, a KBe2 BO3 F2 ‐type six‐membered ring structure is perfectly maintained. In the structure of BaLiZn3 B3 O9, the interlayer connection between adjacent (LiZn3 B3 O16 )∞ layers contains not only Ba–O ionic bonds but also Zn‐O covalent bonds, which help to overcome the plate‐like growth nature of KBe2 BO3 F2 ‐type polyborates. Abstract : Finding new KBe2 BO3 F2 ‐type optical crystals with lump‐growth habit is of great importance to the development of UV and deep‐UV optics. In this communication, we succeeded in bringing the Li/Zn‐O type bonds into the interlayer connection system of a new mixed‐cation KBe2 BO3 F2 ‐type zinc‐borate, BaLiZn3 B3 O9, which is featured with a three‐dimensional (LiZn3 B3 O9 )∞ network and shown to exhibit a lump‐growth habit.